2014
DOI: 10.1016/j.pharep.2013.06.003
|View full text |Cite
|
Sign up to set email alerts
|

The influence of mianserin on TNF-α, IL-6 and IL-10 serum levels in rats under chronic mild stress

Abstract: The results confirm an increase in proinflammatory cytokines in the blood of rats with experimentally induced depression and show the protective role of the activity of mianserin on the cytokine levels, expressed in a lowering of TNFα and IL-6 levels in stressed animals, and of IL-10 levels after LPS administration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 41 publications
0
26
1
1
Order By: Relevance
“…Our study does not confirm the data showing that the levels of IL-6 in patients with depressive disorders are higher than in healthy individuals [5][6][7][8][9][10][11]. The results obtained in our study also differ from the observations of researchers who believe that treatment with mianserin [28], amitriptyline [31] and SSRI [13] reduces the concentration of TNF-α in patients with depression, compared to its pre-treatment values .…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…Our study does not confirm the data showing that the levels of IL-6 in patients with depressive disorders are higher than in healthy individuals [5][6][7][8][9][10][11]. The results obtained in our study also differ from the observations of researchers who believe that treatment with mianserin [28], amitriptyline [31] and SSRI [13] reduces the concentration of TNF-α in patients with depression, compared to its pre-treatment values .…”
Section: Resultscontrasting
confidence: 99%
“…It was demonstrated in an animal model study that administration of mianserin to rats with experimentally induced depression resulted in a significant reduction in the concentrations of IL-6 and TNF-α [28]. Służewska et al [29] observed reduced concentrations of IL-6 in depressed patients undergoing treatment with fluoxetine compared to pretreatment values.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the multiple neurochemical changes that occur in response to stress, excessive inflammation processes is thought to play a major role in stressinduced cognitive impairments. Several studies have reported that exposure to stress increased the hippocampal [9,34,51] and plasma TNF-␣ levels [52]. Accumulating evidence indeed supports a relationship between inflammatory cytokines and various types of learning and memory.…”
Section: Discussionmentioning
confidence: 96%
“…One study has shown a decrease in TNF-α levels with selective serotonin re-uptake inhibitors treatment [19] . One preclinical study has shown that mianserin treatment resulted in a significant lowering of TNF-α in the blood of rats in an experimental model of depression [29] .…”
Section: Discussionmentioning
confidence: 99%